2011
DOI: 10.1080/13557858.2011.578734
|View full text |Cite
|
Sign up to set email alerts
|

The re-shaping of the life-world: male British Bangladeshi smokers and the English smoke-free legislation

Abstract: For maximum impact, tobacco control interventions aimed at whole populations may need to be supplemented by culturally sensitive measures in local areas where there is a high concentration of Bangladeshi people. Similar considerations may apply to other minority communities with a high prevalence of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Research has also reported on perceptions of young people vis-à-vis WTS legislation. 148 164 Participants in focus group discussions in Lebanon and England noted the importance of legislation in curbing WTS among young persons and stated that the different approaches of governments in legislating cigarettes versus waterpipes promote the idea that one is a safer alternative than the other. They also cautioned that the passage of a law is only the first step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also reported on perceptions of young people vis-à-vis WTS legislation. 148 164 Participants in focus group discussions in Lebanon and England noted the importance of legislation in curbing WTS among young persons and stated that the different approaches of governments in legislating cigarettes versus waterpipes promote the idea that one is a safer alternative than the other. They also cautioned that the passage of a law is only the first step.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in coverage and application of tobacco control laws to cigarettes and waterpipe may limit comprehensive tobacco control efforts as individuals may merely shift their smoking patterns from one tobacco product to another. 164 …”
Section: Resultsmentioning
confidence: 99%
“…Prev. Cessation 2019;5(August):26 https://doi.org/10.18332/tpc/110586 stated that government legislation could be a significant step toward reducing the prevalence of hookah smoking 54 . In a review of the laws in 62 countries, only the United States, United Kingdom, India, United Arab Emirates and Pakistan had passed influential laws controlling hookah smoking 55 .…”
Section: At the Political Levelmentioning
confidence: 99%
“…including United States [4,[22][23][29][30][31][32][33][34][35][36][37][38], United Kingdom [21,[39][40][41][42][43], Germany [6,44], Iran [45][46], Egypt [47][48], Malaysia [49], India [50], Dutch [51], Pakistan [52], Qatar [53], Jordan [10], Lebanon [54], Syria [55], Turkey [56], Bahrain [57], Israel [58], United Arab Emirates [22], Saudi Arabia [59],…”
Section: Resultsmentioning
confidence: 99%